Visual Event-Related Potentials in Mild Cognitive Impairment and Alzheimer's Disease: A Literature Review - Morrison, Cassandra; Rabipour, Sheida; Taler, Vanessa; Sheppard, Christine; Knoefel, Frank (Current Alzheimer Research, 2019)
Background: Cognitive deficits are correlated with increasing age and become more pronounced for people with mild cognitive impairment (MCI) and dementia caused by Alzheimer's disease (AD). Conventional methods to diagnose cognitive decline (i.e., neuropsychological testing and clinical judgment) can lead to false positives. Tools such as electroencephalography (EEG) offer more refined, objective measures that index electrophysiological changes associated with healthy aging, MCI, and AD. Objective: We sought to review the EEG literature to determine whether visual event-related potentials (ERPs) can distinguish between healthy aging, MCI, and AD. Method: We searched Medline and PyscInfo for articles published between January 2005 and April 2018. Articles were considered for review if they included participants aged 60+ who were healthy older adults or people with MCI and AD, and examined at least one visually elicited ERP component. Results: Our search revealed 880 records, of which 34 satisfied the inclusion criteria. All studies compared cognitive function between at least two of the three groups (healthy older adults, MCI, and AD). The most consistent findings related to the P100 and the P3b; while the P100 showed no differences between groups, the P3b showed declines in amplitude in MCI and AD. Conclusion: Visually elicited ERPs can offer insight into the cognitive processes that decline in MCI and AD. The P3b may be useful in identifying older adults who may develop MCI and AD, and more research should examine the sensitivity and specificity of this component when diagnosing MCI and AD.
Keywords: Alzheimer' s disease